Agronomic and sensory evaluation of lettuce in hydroponic system (Bioscience Journal, 2021)
Lettuce is the most important leafy vegetable in Brazil. Hydroponic lettuce cultivation has grown due to the viability of harvesting throughout the year. In this context, this study aimed to evaluate the agronomic characteristics, color, and preference of curly lettuce in the NFT hydroponic system. Six lineages (6601-1A, 6601-2L, 7016-6A, 7119-1B, 7223-1A, and 7224-4A) and two commercial cultivars (Brida and Vanda) of lettuce were used, in a completely randomized blocks design with four replications. Shoot length, root length, stem length, number of leaves, stem diameter, plant diameter, shoot fresh mass, root fresh mass, chlorophyll content, instrumental color, and sensory characteristics were evaluated. As for agronomic evaluation, the bolting of 6601-2L lettuce was relevant in different attributes. The Vanda lettuce and the lineage 7016-6A presented best performances for shoot fresh mass (399.44 and 378.63 g, respectively), while the lineages 7119-1B and 6601-2L present the worst performance (279.50 and 273.13 g, respectively). There was variation in chlorophyll content and luminosity, however, the evaluators did not notice differences between lettuces for brightness or green color, as well as for crunchy texture. Lettuces 6601-2L, 7224-4A, 6601-1A, Brida, 7223-1A, and 7119-1B were preferred. The variation among plants may be due to different situations, such as harvesting times and bolting, and a direct relationship between agronomic properties and preference among lettuces has not been established yet.